2011
DOI: 10.1093/carcin/bgr125
|View full text |Cite
|
Sign up to set email alerts
|

Urinary levels of the tobacco-specific carcinogen N'-nitrosonornicotine and its glucuronide are strongly associated with esophageal cancer risk in smokers

Abstract: N'-Nitrosonornicotine (NNN) and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) are tobacco-specific nitrosamines. NNN and NNK can induce cancers of the esophagus and lung, respectively, in laboratory animals, but data on human esophageal cancer are lacking. The association between levels of NNN and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), an NNK metabolite, in urine samples collected before diagnosis and risk of esophageal cancer was examined in 77 patients with esophageal cancer and 223 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 27 publications
5
98
1
Order By: Relevance
“…In agreement with these results, the treatment of rats with (S)-NNN in our recent study produced a 100% incidence of oral and esophageal tumors, compared with only 5 and 3 out of 24 rats developing oral and esophageal tumors, respectively, upon treatment with (R)-NNN (Balbo et al, 2012). The relevance of these animal data to humans is supported by the findings of the strong relationship between NNN exposure in smokers and risk of esophageal cancer in a prospective cohort (Yuan et al, 2011), as well as by the epidemiological evidence that smokeless tobacco products contaminated with high levels of NNN cause oral cancer (Gupta, Murti, & Bhonsle, 1996;IARC, 2007;Stepanov, Hecht, Ramakrishnan, & Gupta, 2005).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In agreement with these results, the treatment of rats with (S)-NNN in our recent study produced a 100% incidence of oral and esophageal tumors, compared with only 5 and 3 out of 24 rats developing oral and esophageal tumors, respectively, upon treatment with (R)-NNN (Balbo et al, 2012). The relevance of these animal data to humans is supported by the findings of the strong relationship between NNN exposure in smokers and risk of esophageal cancer in a prospective cohort (Yuan et al, 2011), as well as by the epidemiological evidence that smokeless tobacco products contaminated with high levels of NNN cause oral cancer (Gupta, Murti, & Bhonsle, 1996;IARC, 2007;Stepanov, Hecht, Ramakrishnan, & Gupta, 2005).…”
Section: Resultssupporting
confidence: 80%
“…Existing scientific evidence indicates that the tobacco-specific nitrosamine N′-nitrosonornicotine (NNN) plays an important role in the induction by tobacco products of cancers of the esophagus and oral cavity (Hecht, 1998; International Agency for Research on Cancer [IARC], 2007;Yuan et al, 2011). In laboratory animals, NNN causes esophageal tumors in rats, nasal cavity tumors in rats and mink, and respiratory tumors in mice and hamsters (Hecht, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…More detailed studies should be performed to determine whether chromosomal changes in NNK-induced animal models are consistent with the changes in lung cancer patients upon tobacco exposure, which may help to find novel biomarkers that are critical for the early detection and risk management of lung cancer. Recent studies revealed that urinary levels of tobacco-specific nitrosamine metabolites could be potentially used to predict risk and development of lung cancer [38][39][40][41][42][43].…”
Section: Nnk Induces Gene Mutation and Chromosomal Instabilitymentioning
confidence: 99%
“…The tobaccospecific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is a potent carcinogen; levels of its metabolite 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), measured in urine, are independently associated with the risk of lung cancer in a large cohort of smokers (Yuan et al, 2009;. Additionally, urine concentration of NNAL has been shown to be predictive of the risk of development of esophageal carcinoma (Yuan, Knezevich, et al, 2011). Urine NNAL has an elimination half-life of 10-18 days, such that tobacco use can be detected for 6-12 weeks after last use (Goniewicz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%